The Dynamics of Skincare Purchasing Decisions: The Mediating Role of Brand Image in the Influence of Product Quality, Price Fairness, and Social Proof - Afrinia Dewi Kusmiarni; Purwanto; Ririn Andriana (LP2M IAIN Palopo, 2026)
The expansion of the Korean skincare market has led to increasingly intense competition among brands in attracting Generation Z consumers. This research investigates how product quality, perceived price fairness, and social proof affect purchasing decisions for SKIN1004 skincare products in Surabaya, with brand image positioned as a mediating variable. A quantitative explanatory design was employed using purposive sampling, involving 190 Generation Z respondents aged 17–28 years who had purchased and used SKIN1004 products. Data were processed through the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique. The results indicate that product quality, price fairness, and social proof positively and significantly influence both brand image and purchase decisions. Price fairness emerges as the most influential factor in shaping brand image and driving purchase decisions, while brand image partially mediates these relationships. These findings indicate that Generation Z's purchasing decisions are shaped not only by perceptions of product quality but also by perceptions of price fairness, social influence, and the brand image formed through digital interactions. The study provides managerial implications for skincare brands in designing pricing strategies, strengthening digital engagement, and building a competitive brand image in e-commerce markets.